PENGARUH MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) PADA PEMBELAJARAN DARING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DITINJAU DARI KEMAMPUAN AWAL MATEMATIKA SISWA - Juniarisandy Saragih; Pinta Deniyanti S; Tian Abdul Aziz (UIN Sumatera Utara Medan, 2022)
The implementation of this study aims to assure the effect of CIRC learning model on students mathematics communication ability based on prior knowledge. The design of reseach is quasi-experimental design with the population is all students in MTsN District of Cakung Academic Year 2020/2021. The research sample chosen by multisage random sampling is students of class VIII-1 MTsN 20 and VIII-2 MTsN 28 as the experiment class and class VIII-2 MTsN 20 and VIII-1MTsN 28 as the control class. Average value mathematics communication ability of the students in experiment class 14.38 and control class 11.35. Based on data interpretation and analysis t-test with a significant value (α) = 0,05, the value is Sig = 0.049, so that Sig < α. With these results it was concluded that there was an effect of the CIRC learning model on the mathematical communication ability of class VIII MTsN students in Cakung District